Evaluation of superior-inferior position of mandibular canal and its anatomic variations on panoramic radiographs in patients over 18 referring to Khorasgan Dental School - Roshanak Ghafari; Ahmad Motaghi; Mehdi Elahi; Sima Saghaie (Isfahan University of Medical Sciences, 2011)
Introduction: Attention to the location and the shape of mandibular canal is necessary to prevent problems during mandibular surgeries. This study was determined the prevalence of superior-inferior position of mandibular canal and its anatomic variations on panoramic radiographs in patients over 18 referring to Khorasgan Dental School.Materials and methods: In this descriptive-analytical study 260 radiographs were examined for variations in the position of mandibular canal. The subjects' personal data, type of mandibular canal regarding its position based on Nortje's classification (high, low or intermediate position in relation to the apex of the first molar root and inferior border of the mandible), the distance from the superior border of lingula to the center of the ramus, existence of bifid canal and its shape and side and existence of anesthesia problems or impacted teeth on the same side as the bifid canal, were recorded. Data was analyzed by SPSS 10, using chi-squared test (α=0.05).Results: The most common canals in relation to their position relative to the first molar area, in descending order, were canals in middle position (55.8%), in the low position (35%), and in the high position (9.2%), respectively. No statistically significant differences were observed between the frequency distributions of canal positions (p value = 0.14%). The average distances from the superior border of lingula to the center of the ramus, in low position, middle position, and high position canals were 10.7, 11.35, and 10.87 mm, with no statistically significant differences (p value = 0.14). Conclusion: According to the results, there were no statistically significant differences between the frequency distributions of different positions of mandibular canals in relation to the root apex of the first molar and also between the distances from the lingual to the center of the ramus. Similar studies using CT scan technique are recommended. Key words: Inferior alveolar nerve, Mandible, Panoramic radiography.